Nonlinear reduced order modeling for nonlinear response simulation of panels via Large Eddy Simulation - Xu, Wei; Xu, Min; An, Xiaomin; Yao, Weigang (Journal of sound and vibration, 2021)
Supersonic vehicles are subject not only to aerodynamic heating, but also to different acoustics, one of which is aeroacoustic induced by pressure fluctuation of high speed flow. The state-of-art structure sonic fatigue analysis is conducted by using uniformly distributed random White Gaussian Noise (WGN). However, uniformly distributed excitation is usually not consistent with the actual situation, and the validity of the method needs further investigation. In the present study, a nonlinear reduced-order model (NLROM) is presented to compute nonlinear response of isotropic and composite plates. The NLROM is based on finite element (FE) model and is constructed by means of Galerkin projection of the full order system onto a small subspace. The input of the NLROM is aerodynamic and aeroacoustic loads, which are computed by Large Eddy Simulation (LES) and interpolated from aerodynamic grid to structure node by using Radial Basis Function (RBF). The nonlinear response of the isotropic and composite plates is computed by NLROM and compared with WGN. The results show that the NLROM offers nearly an order of magnitude speed up as compared with direct FE simulation and predicts shorter sonic fatigue life than WGN. •A nonlinear reduced order model (NLROM) is developed for sonic fatigue analysis.•Aeroacoustic computed by LES and WGN are considered as acoustic excitation and the input of the constructed NLROM.•The nonlinear response of isotropic and composted plate is computed by NLROM and compared against the finite element model (FEM).